Analysis of Mathematical Communication Skills Viewed from Student Learning Styles in Eighth Grader Students in Learning Resource Based Learning Model - Anintya, Yolanda Astrid; Pujiastuti, Emi; Mashuri, Mashuri (Department of Mathematics, Universitas Negeri Semarang, 2017)
Tujuan penelitian ini adalah untuk mengetahui kemampuan komunikasi matematis siswa pada model resource based learning berdasarkan ketuntasan dan gaya belajar. Gaya belajar yang dimaksud adalah gaya belajar visual, auditorial dan kinestetik. Metode penelitian yang digunakan adalah mixed methode, dengan squential explanatory desain. Populasi dalam penelitian ini adalah siswa kelas VIII SMP 1 Jekulo dan pengambilan sampel dilakukan dengan random sampling. Sampelnya adalah kelas VIII-E dan subjek penelitian dipilih dengan teknik purposive, diperoleh 6 subjek yang terbagi untuk tiap gaya belajar. Hasil penelitian menunjukkan bahwa (1) kemampuan komunikasi matematis siswa dengan model pembelajaran resource based learning mencapai ketuntasan klasikal, (2) kemampuan komunikasi matematis siswa dengan gaya belajar visual dapat dikategorikan dalam tingkat pencapaian 4, (3) kemampuan komunikasi matematis siswa dengan gaya belajar auditorial dapat dikategorikan dalam tingkat pencapaian 4,(4) kemampuan komunikasi matematis siswa dengan gaya belajar kinestetik dapat dikategorikan dalam tingkat pencapaian 3. The purpose of this research was to know the students ability of mathematical communication on a learning with resource based learning model that is based on the criteria of completeness and the learning styles. These learning style are visual, auditory and kinesthetic. This research used a mixed methods, and squential explanatory design. The population of this reseacrh are students of VIII grade SMP 1 Jekulo and the sample was taken by random sampling. The sample was VIIIÂE class and subjects were selected by purposive, it was obtained 6 subjects that divided in each learning styles. The results showed that (1) the ability of mathematical communication students with resource based learning model achieved classical completeness, (2) the students ability of mathematical communication with a visual learning style can be categorized in the fourth level of achievement,(3) the students ability of mathematical communication with learning styles auditory can be categorized in the fourth level of achievement, (4) the students ability of mathematical communication with kinesthetic learning style can be categorized in the third level of achievement.